Revolution and counterrevolution in Poland, 1980-1989 : Solidarity, martial law, and the end of communism in Europe - Paczkowski, Andrzej, 1938- (Rochester studies in East and Central Europe, 2015)
"Examines the 1980 Solidarity revolution in Poland, the government's subsequent establishment of martial law in response, in 1981, and the eventual transition to democracy in 1989"--Provided by publisher